Immunity against Pasteurella multocida in Animals Vaccinated with Inactivated Pasteurella multocida and Herbal Adjuvant 'DIP-HIP' - Himanshi Tanwar; Anand Prakash Yadav; Brijbhushan; Shweta; Shashi Bala Singh; Lilly Ganju (Journal of Vaccines and Immunology - Peertechz Publications, 2016)
Background: Haemorrhagic septicaemia (HS) is acute, highly contagious form of disease of water buffalo, cattle, and bison caused by Pasteurella multocida (PM). It is considered the most economically important bacterial disease of cattle and buffalo, .in tropical areas of Asia, particularly in Southeast Asia. PM is a gram-negative coccobacillus, belonging to Pasteurellaceae family. PM is transmitted either during direct contact or via fomites by ingestion or inhalation via contaminated feed and water. Currently, there are no broadly protective vaccines -adjuvant formulation with long-lasting immunity available against HS. Aluminium-based mineral salts such as alum are the only immunologic adjuvants. Herbal adjuvants are evaluated extensively to replace the classical adjuvants being safe and efficacious. Result: In the present study, one herbal adjuvant DIP-HIP is evaluated with inactivated PM (iPM) antigen as vaccine in both small (mice) as well as big (cattle) animals for its efficacy. The results suggest that after single booster DIP-HIP + iPM emulsion gave maximum antibody titres in comparison to iPM alone or Alum + iPM in both mice as well as seronegative cattle. To further confirm the potential of DIP-HIP adjuvant formulation with iPM antigen in providing protection against HS, the median lethal dose (LD50) of PM was determined (1 X 107 CFU/ml), following which DIP-HIP + iPM emulsion immunized mice were challenged with this dose. The DIP-HIP containing formulation turned out to be broadly protective against HS with long-lasting immunity. Conclusion: DIP-HIP is a potential adjuvant, which can be used in HS vaccines to provide extended immunity.